GE_GERICHTE C/20221/2016 vom 12. November 2018 - GE Cour de justice (2018)
BAIL À LOYER ; LOGEMENT SOCIAL ; SOUS-LOCATION ; SÉJOUR ILLÉGAL ; ABUS DE DROIT ; RÉSILIATION ; PROLONGATION | CO.266a.al2; CO.266c; CO.271s; CC.2.al2; CO.272.al1